Measuring sustainable development in the selected Organization of Islamic Cooperation (OIC) countries based on maqasid al-shari'ah - Khan, Foyasal (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2020)
In 2015, a set of 17 Sustainable Development Goals (SDGs) was approved as a new global agenda from 2016 to 2030. It is found that SDGs mainly cover three dimensions-economic, social, and environmental-of Sustainable Development (SD) and ignore religious-spiritual dimension. Based on a survey of literature, one of the key findings of the study is that teachings and values of the four major religions (Buddhism, Christianity, Hinduism and Islam) are relevant to SD and thus, religion has enormous potential to play a positive decisive role in achieving SDGs. For evaluating the sustainability performances of the Organization of Islamic Cooperation (OIC) member countries, this thesis constructs a Maqasid Al-Shari'ah based SD framework using al-Ghazali's theoretical framework of Maqasid Al-Shari'ah. From the framework, an index, Maqasid Al-Shari'ah based Sustainable Development Index (MSSDI) is built. MSSDI has five dimensional sub-indexes: Hifdh al-Din (Protection of Religion), Hifdh al-Nafs (Protection of life), Hifdh al-'Aql (Protection of Intellect), Hifdh al-Nasl (Protection of Progeny) and Hifdh al-Mal (Protection of Property). Due to constraints of data, especially related to Hifdh al-Din and spiritual needs of Hifdh al-Nafs, only 12 countries were analysed for MSSDI in all dimensions. The major findings are: Malaysia, Jordan, and Morocco are the top three performers in MSSDI. The dimensional and overall indexes show that lower-middle income and low-income countries are more vulnerable in terms of various aspects of sustainability. Hence, a greater cooperation and partnership among the OIC member countries is urgent to realize SDGs collectively. It is expected that the findings will guide policymakers substantially to design an appropriate policy framework to address all the issues associated with religion and SD in the OIC member countries.